Influencing factors affecting health-promoting lifestyles in patients with primary liver cancer: a latent profile analysis - Xuerui Wang; Jiarong Ding; Liping Zhou; Qiaomei Fu; Ye Zhang; Yao Lu (Scientific Reports)
Abstract To explore the potential profile categories of health promoting lifestyle in patients with primary liver cancer and analyze the influencing factors of different categories. Primary liver cancer patients who visited a tertiary hospital in Nanjing from October 2021 to May 2023 were selected as the survey subjects. A general information questionnaire and a health-promotion lifestyle scalewere used for data collection. Potential profile analysis was conducted to classify the health-promoting lifestyles of patients with primary liver cancer, and the influencing factors of different categories were explored through univariate analysis and multiple logistic regression analysis. Clinical registration trial number: ChiCTR2400079823 (12/01/2024). A total of 328 questionnaires were collected, of which 324 were valid, resulting in a validity rate of 98.78%.The latent profile analysis indicates that the health promotion lifestyle of primary liver cancer patients can be categorized into three potential profiles: “low health promotion neglect” (n = 128, 39.5%), “moderate health promotion balance” (n = 87, 26.9%), and “high health promotion lone hero” (n = 109, 33.6%). The influencing factors include educational level, per capita monthly income, disease-related economic burden, postoperative duration, work status, sleep disorders, and whether neoadjuvant therapy was administered preoperatively (P < 0.05). Conclusion: There is significant heterogeneity in the health promotion lifestyles of patients with primary liver cancer. Nursing staff should develop targeted health promotion strategies, focusing on improving patients’ health behaviors to enhance their quality of life.